Penaksiran Luas Bidang Dasar Pada Tegakan Jati Dengan Menggunakan Parameter Tinggi, Diameter Tajuk Dan Jumlah Pohon Melalui Foto Udara - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
The objective of this research was to find out the relationship between basal area (BA) and other parameters of stand namely stand height, crown diameter and number of tree. Unlike stand height, crown diameter and number of tree, stand basal area or stem diameter was not measurable through aerial photographs. They influenced stem diameter growth and had relationship with stand basal area as well. Therefore it was possible to predict stand basal area. This research was carried out in teak plantation of Cabak Forest Resort, Cepu Forest District, Forest State Enterprise Unit I Central Java. Data were collected from various stand age (VI, VII dan VIII) with a uniform site index (31/2) and sample plots of 0.1256 ha each, were distributed proportionally over the whole stand area. Plots made on the aerial photographs were cross checked on the ground. The stand basal area was estimated based on the data of stem diameter measured on the ground plots, while stand height, crown diameter and tree number were measured on the aerial photographs. The result was a regression equation : Lbds = - 0.4047 + 0.0411 T + 0.0227 Dt2 With R2 = 58.18 % and SE = 0.2896 m2 each plot.